P.057 Solely neonatal hypoxic ischemic encephalopathy or more? A study examining genetic predisposition towards a clinical picture of HIE. (5th June 2019) - Woodward, KE; Murthy, P; Mineyko, A; Mohammad, K; Esser, M
Abstract : Background: Neonatal hypoxic ischemic encephalopathy (HIE) is a clinical phenomenon, that often results from pre or perinatal reduced cerebral blood flow and/or hypoxemia. However, in some cases, neonates present with HIE without significant risk factors or have an unusual clinical course. With the advent of advanced genetic testing, we aimed to explore if such infants had genetic risk factors predisposing them to an HIE-phenotype.Methods: We reviewed 206 charts of infants meeting local protocol criteria for moderate to severe HIE at Level III NICU's in Calgary, Alberta. Of these, 27 patients had genetic testing such as microarray, whole exome sequencing, or gene panels.Results: Six/twenty-seven patients had genetic mutations; two CDKL5 mutations (protein kinase), one CFTR mutation (cystic fibrosis), one PDH deficiency, one CYP21A2 mutation (congenital adrenal hyperplasia), and one ISY1 (VUS; pre-mRNA splicing). Two patients had noted difficult deliveries and four had minor complications, but all were out of keeping with the severity of presumed HIE.Conclusions: This preliminary study demonstrates a possible association between genetic co-morbidities and predisposition towards HIE in the context of a relatively uneventful pre/perinatal course. Earlier identification of genetic etiology, recognized by a discrepancy between risk factors and clinical presentation, could aid in treatment decisions and outcome prognostication.